Dikotomi Pemilihan Kepala Daerah: Demokrasi dan Dinasti Perspektif Islam - Jamaludin, Jujun (SIYASI: Jurnal Trias Politica, 2023)
Indonesia is a large country and is crowned as the largest archipelagic country inthe world. Indonesia consists of various ethnic groups, languages and religions.However, when the local elections take place, different perceptions from thecommunity often arise, issues that often occur include: legal issues, historicalissues, and "Syara" religious issues. Political dynasties are not the right system toapply to the State of Indonesia, because the State of Indonesia is not a countrywith a monarchical system of government that elects leaders based on lineage butdemocracy or elections. Muslims in Indonesia more easily accept democracy,because democracy is not related to and does not conflict with the rules of Fiqhand Sufism. The purpose of organizing elections is to achieve an orderly andpeaceful transition of government leadership, replacement of officials who willrepresent the interests of the people, implement the principle of people'ssovereignty, and implement the principle of citizens' human rights. The process ofchange in the Regional Head Election will certainly bring positive and negativeimpacts. The positive impact is that people will be more mature and independentin choosing their future leaders. While the negative impact requires a sizableelection fund, prone to commotion and disruption of the bureaucracy ingovernment. Indonesia merupakan negara besar dan dinobatkan sebagai negara kepulauanterbanyak di dunia. Indonesia terdiri dari berbagai suku bangsa, bahasa, danagama. Namun Ketika pilkada berlangsung seringkali muncul persepsi yangberbeda dari masyarakat, isu-isu yang sering terjadi diantaranya: Isu hukum,Isu sejarah, dan Isu agama “Syara”. Dinasti politik bukanlah sistem yang tepatuntuk diterapkan di Negara Indonesia, sebab negara Indonesia bukanlahnegara dengan sistem pemerintahan monarki yang memilih pemimpinberdasarkan garis keturunan melainkan demokrasi atau pemilihan. umat Islamdi Indonesia lebih mudah menerima demokrasi, karena demokrasi tidakberkaitan dan tidak bertentangan dengan aturan-aturan Fiqih dan tasawuf.Tujuan penyelenggaraan pemilu Mewujudkan peralihan kepemimpinanpemerintahan secara tertib dan damai, Pergantian pejabat yang akan mewakilikepentingan rakyat, Mengimplementasikan prinsip kedaulatan rakyat, danMelaksanakan prinsip hak-hak asasi warga negara. Proses perubahan dalamPemilihan Kepala Daerah ini, tentu akan membawa dampak positif dannegative. Dampak positifnya masyarakat akan lebih dewasa dan mandiri dalammemilih calon pemimpinnya. Sedangkan dampak negatif membutuhkan danapemilu yang cukup besar, rawan keributan dan terganggunya birokrasi dalampemerintahan.